The effect of body mass index on blood loss and complications in simultaneous bilateral total hip arthroplasty: A multicenter retrospective study. (17th November 2021) - Cao, Guorui; Yang, Xiuli; Yue, Chen; Tan, Honglue; Xu, Hong; Huang, Zeyu; Quan, Songtao; Yang, Minglu; Pei, Fuxing
Background: The effect of body mass index (BMI) on blood loss in simultaneous bilateral total hip arthroplasty (SBTHA) was still undetermined. The purpose of the study was to evaluate the blood loss, transfusion and incidence of complications in normal, overweight, and obese patients undergoing SBTHA. Methods: A total of 344 patients following SBTHA were enrolled into this study. The patients were assigned into three groups on the basis of their BMI, including normal (BMI 18.0–24.9 kg/m 2 ), overweight (BMI 25.0–29.9 kg/m 2 ), or obese group (BMI ≥ 30.0 kg/m 2 ). The primary outcome was total blood loss (TBL), and secondary outcomes were intraoperative blood loss, drain volume, ratio of TBL and patient's blood volume (PBV), transfusion rate and volume, hemoglobin and hematocrit drop, length of stay, expenses, and complications. Results: The PBV and TBL increased significantly along with the elevated BMI ( p < 0.001; p = 0.019, respectively). There was no significant difference in intraoperative blood loss, drain volume, transfusion volume, length of stay, expenses, or incidence of complications among the three groups. In addition, the transfusion rate in normal group was higher than that in overweight (58.3% vs 39.6%, p = 0.001) and obese group (58.3% vs 31.9%, p = 0.001). The maximum hemoglobin drop in obese group was the highest ( p = 0.001). Conclusion: Obesity could increase perioperative blood loss but not increase transfusion risk in the setting of SBTHA. Conversely, obese and overweight patients maybe have lower transfusion need compared with normal patients because of more blood volume. In addition, obesity did not affect the incidence of complications.